Study of the decomposition of supported nickel acetylacetonate by thermal techniques - Nichio, Nora Nancy (2003)
The decomposition of supported nickel acetylacetonate (AcacNi) was studied by using thermal techniques to evaluate the nature of the calcination products. Thermogravimetric techniques used in this work indicated transformations occurring during preparation and calcination steps. Results demonstrated the important influence of support modifications upon the catalyst nature finally obtained. © 2002 Elsevier Science B.V. All rights reserved.